Prevalence and clinico-pathological parameters of PPR infected goats and their response to antibiotic treatment at Panchlaish, Chittagong, Bangladesh - Naznin, M; Ahaduzzaman, M; Chowdhury, S; Biswas, PK (International Journal of Natural Sciences, 2016)
The present study was conducted in the Panchlaish Upazilla Veterinary Hospital of Chittagong district during the period of July to September, 2013 to find out the prevalence and clinico-pathological findings of Peste des petits ruminants (PPR) in goats, and to observe the response of PPR-goats to different treatments. During the course of study 202 goats were examined of which 98 were PPR positive. Diagnosis of a PPR case was made following the clinical examinations. The results showes that the median age of PPR-goats was higher compared with the healthy ones. The median per-rectum temperature, heart and respiratory rates were also higher in the the PPR-postive goats. No significant difference was seen on its prevalence in goats belonging to Black Bengal or Jamunapari breeds. Its occurence was also evenly seen in each of the three months-July, August and September. But, prevalence of PPR was significantly higher in the non-vaccinated goats. Some hematological parameters except neutrophil count was lower in PPR goats. The recovery rate from clinical signs was higher in goats treated with parenteral administration of oxytetracycline. International Journal of Natural Sciences (2014), 4(2) 1-7